DETERMINING THE EFFECTIVENESS OF VARIOUS INTENSIVE AGRO- TECHNOLOGIES FOR SUSTAINABLE GRAIN PRODUCTION OF SPRING BARLEY IN THE STEPPE CONDITIONS OF UKRAINE - Chuhrii, H. A. (Scientific Progress & Innovations, 2021)
The article defines the effectiveness of various intensive agro-technologies for sustainable grain production of spring barley. Meteorological conditions for the growing season of spring barley over the years of research were analyzed. It has been established that over the study years, the process of obtaining seedlings took place under relatively optimal conditions. Against the background of humidity increase, the weak root system of spring barley did not actively penetrate into the deeper soil layers due to“favorable” conditions on the surface. During booting, coming into ear, flowering and the beginning of grain formation, the time when spring barley was the most moisture demanding, high temperatures were observed – the drought. It has been determined that these conditions resulted in a significant yield decrease. The obtained data indicate the ability of plants to resist negative phenomena at improving nutritional conditions, acting as a regulator in maintaining the physiological balance of spring barley crops. It has been analyzed that the most positive effect was observed during the experiments with an intensive feeding system, which affects the formation of a larger number of productive stems. Thus, in all the studied variants, an increase was obtained from 16.8 to 37.3 %. The coefficient of productive tillering was the largest on variant 9, while variant 8 was the worst as to this indicator. It has been proven that for the yield formation, the main thing is the transition of the stem growing point from vegetative to generative phase of growth and the formation of the main yield components. It has been determined that the use of the preparations under the study contributed to the enhancement of adaptation processes in spring barley plants. The effectiveness of the impact of these preparations has been proven by an increase in biometric indices, indicators of the yield structure and, as a result, the yield of spring barley.